New glasses in the system InF3-BaF2-ErPO4 - Messaddeq, Younes [UNESP]; Moya, C. M.; Melnikov, P.; Ribeiro, SJL (Spie - Int Soc Optical Engineering, 1998)
New glasses have been obtained in the system InF3-BaF2-ErPO4. Glass compositions with up to 30% mol Er3+ were shown to exist and characterized by thermal analysis, x-ray: diffraction, IR absorption and electronic spectroscopy. The systems with high Er3+ content were studied recording IR and visible emission spectral characteristics. A specially elaborated technique allowed the preparation of a high purity phosphate precursor ErPO4. X-ray identification of the crystalline phases appearing during thermal treatment have been carried out and parameters of a mixed fluoride Ba4In3-nErnF17 calculated.
Keywords: fluorophosphate glasses; erbium; infrared emission